Criteria for Educational Projecting in Social and Health Services - Simone, Maria Grazia (Modern Perspectives in Language, Literature and Education Vol. 7, 2021)
The goal of the article is to reflect on the meaning of the action of projecting in socio-educational services and in environments that take care of the health of citizens, children, vulnerable people. The result that the article reaches is to offer a series of useful criteria for those who have to design within this kind of services that take care of the often vulnerable person.